In the moonlight: non-catalytic functions of ubiquitin and ubiquitin-like proteases - Campos Alonso, Marta; Knobeloch, Klaus-Peter (Frontiers in Molecular Biosciences, 2024)
Proteases that cleave ubiquitin or ubiquitin-like proteins (UBLs) are critical players in maintaining the homeostasis of the organism. Concordantly, their dysregulation has been directly linked to various diseases, including cancer, neurodegeneration, developmental aberrations, cardiac disorders and inflammation. Given their potential as novel therapeutic targets, it is essential to fully understand their mechanisms of action. Traditionally, observed effects resulting from deficiencies in deubiquitinases (DUBs) and UBL proteases have often been attributed to the misregulation of substrate modification by ubiquitin or UBLs. Therefore, much research has focused on understanding the catalytic activities of these proteins. However, this view has overlooked the possibility that DUBs and UBL proteases might also have significant non-catalytic functions, which are more prevalent than previously believed and urgently require further investigation. Moreover, multiple examples have shown that either selective loss of only the protease activity or complete absence of these proteins can have different functional and physiological consequences. Furthermore, DUBs and UBL proteases have been shown to often contain domains or binding motifs that not only modulate their catalytic activity but can also mediate entirely different functions. This review aims to shed light on the non-catalytic, moonlighting functions of DUBs and UBL proteases, which extend beyond the hydrolysis of ubiquitin and UBL chains and are just beginning to emerge.